2017
DOI: 10.1016/j.jid.2017.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Human Keratinocyte Differentiation Requires Translational Control by the eIF2α Kinase GCN2

Abstract: Appropriate and sequential differentiation of keratinocytes is essential for all functions of the human epidermis. While transcriptional regulation has proven to be important for keratinocyte differentiation, little is known about the role of translational control. A key mechanism for modulating translation is through phosphorylation of the α subunit of eIF2. A family of different eIF2α kinases function in the integrative stress response to inhibit general protein synthesis coincident with preferential transla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 69 publications
2
14
0
Order By: Relevance
“…N-TERT cells are proliferative human epidermal keratinocytes that are useful and reliable surrogates for primary keratinocytes ( Collier et al. , 2015 , 2017 ; Loesch et al. , 2016 ) and therefore represent skin cells that can propagate UVB-induced mutations that initiate cancer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…N-TERT cells are proliferative human epidermal keratinocytes that are useful and reliable surrogates for primary keratinocytes ( Collier et al. , 2015 , 2017 ; Loesch et al. , 2016 ) and therefore represent skin cells that can propagate UVB-induced mutations that initiate cancer.…”
Section: Resultsmentioning
confidence: 99%
“…, 2013 ) using validated Sigma Mission shRNA clones TRCN0000287091, TRCN0000300850, and TRCN0000262380, respectively. We previously reported knockdown and characterization of these eIF2α kinases using these shRNAs in N-TERT cells ( Collier et al. , 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…This translational control scheme allows for a rapid programing of gene expression and insures that resources are best utilized for full implementation of the ISR. In other organisms, this translational control can also play a role in cell differentiation by processes that involve activation of the ISR [47] and this activity appears to be a major consequence of ISR activation in apicomplexan parasites. Here, we illustrate the importance of latency to the life cycles and transmission of Toxoplasma and Plasmodium , as well as how stress and environmental sensing play an essential role in the conversion towards latency.…”
Section: Post-transcriptional Gene Regulation Is Essential To Parasitmentioning
confidence: 99%
“…While the ISR plays a pro-survival role when induced under a variety of acute stresses, its sustained activation has been implicated in apoptosis and cell differentiation in multicellular organisms [47,37]. Although the downstream targets of the ISR in apicomplexans have yet to be discovered, the upstream components are conserved and underscore the antiquity of this machinery in eukaryotic evolution.…”
Section: Environmental Sensing and The Integrated Stress Responsementioning
confidence: 99%
“…In a preliminary study on keratinocyte differentiation, Collier et al have reported the role of GCN2 phosphorylation-mediated translational control in the normal differentiation and formation of the epidermis. It was observed that the absence of GCN2 disturbed this control over differentiation and therefore could be a cause of various skin diseases, including psoriasis ( 104 ).…”
Section: Regulation Of Amino Acid Signaling During Metabolic and Automentioning
confidence: 99%